CAPTIVE AS AN INSURANCE FORMULA FOR RISK MANAGEMENT: ADVANTAGES AND DISADVANTAGES - R. Holly; E. Greszta (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2017)
This article introduces subject of an insurance captive entity, with focus on how it could be used as insurance formula for risk management. Captive might be the most appropriate insurance formula for risk management. However, the level of achieved success depends on many factors.Insurance captivesare understood as entities which are formed and owned by companies mostly for the purpose of insuring own risks (pure captive or single parent captive). More and more often captives are also formed by a group of companies (group captives) to insure their properties and liabilities towards 3rd parties. Captives are widely used by many companies nowadays. However, many of them,are used solely for a purpose of a risk cession and premium transfer, with an intention to use captivesmore as a profit center in a low taxation country rather than for the purpose of risk management (i.e. a more appropriate role for captive would be to support their owners in enterprise risk management - ERM). This article touches on why captives are not used to their full potential. It may be toochallenging for many decision makers to embrace on captives as risk management formula and extend captives' roles to utilize all possible advantages resulting from owning a captive. Captive can deliver risk management in a more comprehensive way than most commercial insurers on the market. The article also presents advantages and disadvantages of owning an insurance captive.